2008
DOI: 10.1007/s12011-007-8053-z
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Efficacy of Food-Based Calcium Supplementation in Preventing Rickets in Bangladesh

Abstract: To determine whether increased Ca intakes can prevent rickets in a susceptible group of children living in a rickets-endemic area of Bangladesh, we conducted a 13-month long, double-blind, clinical trial with 1-to 5-year-old children who did not present with rickets but ranked in the upper decile of plasma alkaline phosphatase (AP) activity of a screening cohort of 1,749 children. A total of 158 children were randomized to a milk-powder-based dietary supplement given daily, 6 days/week, and providing either 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…Studies carried out in Chakaria, Coxesbazar found that 11 % of children had active rickets and that vitamin D deficiency ranged from 6 to 21 % among the children under 5 years old in that community (18,20) . Additionally a study from same area reported that only 6 % of children (ten out of 158 participants) were suffering from severe vitamin D deficiency (13) , which supports our finding (Table 1). Recently a case-control study (15) was carried out among 1-24-month-old children of northeastern rural Bangladesh and found that 32 % of all children (including cases and controls) were severely vitamin D deficient (<25 nmol/l), with 70 % having serum vitamin D less than 40 nmol/l.…”
Section: Discussionsupporting
confidence: 90%
“…Studies carried out in Chakaria, Coxesbazar found that 11 % of children had active rickets and that vitamin D deficiency ranged from 6 to 21 % among the children under 5 years old in that community (18,20) . Additionally a study from same area reported that only 6 % of children (ten out of 158 participants) were suffering from severe vitamin D deficiency (13) , which supports our finding (Table 1). Recently a case-control study (15) was carried out among 1-24-month-old children of northeastern rural Bangladesh and found that 32 % of all children (including cases and controls) were severely vitamin D deficient (<25 nmol/l), with 70 % having serum vitamin D less than 40 nmol/l.…”
Section: Discussionsupporting
confidence: 90%
“…It has re-emerged as a global public-health concern and is now presumptively linked to a range of infectious, inflammatory and neoplastic diseases throughout the life course and around the world [22]. Country specific sufficient data regarding the use, consumption of calcium and/or vitamin D for Bangladesh is not available though some studies have been conducted for the determination of vitamin D status in infants and children in different regions in Chakaria subdistrict, Cox’s Bazar, Bangladesh [19,23] and Zakiganj subdistrict in Sylhet district [14]. Calcium Research Unit, Department of Food and Environmental Sciences, University of Helsinki performed number of studies on the vitamin D status in women in Bangladesh and has observed a high prevalence of vitamin D deficiency with associated low BMD.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence primarily from developing countries demonstrates that traditional diets low in calcium cause NR [30,43,69,93,[112][113][114] . Therefore, special diets during infancy such as those that avoid milk and dairy products, those using soy or rice milk that are not specifically designed for infants, and/or vegan and macrobiotic diets may predispose infants to NR [115][116][117][118][119][120] .…”
Section: Evidencementioning
confidence: 99%